2017
DOI: 10.1515/fascmath-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Poly-Bernoulli Polynomials of the Second Kind Associated with Hermite Polynomials

Abstract: Abstract. In this paper, we introduce a new class of Hermite multiple-poly-Bernoulli numbers and polynomials of the second kind and investigate some properties for these polynomials. We derive some implicit summation formulae and general symmetry identities by using different analytical means and applying generating functions. The results derived here are a generalization of some known summation formulae earlier studied by Pathan and Khan.Key words: Hermite polynomials, multi-poly-Bernoulli polynomials of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Several authors have shown a growing interest in the exploration and investigation of ∆ h special polynomials, as evidenced by works such as [4,6,9,15,19]. Recently, Shahid Wani et al have made significant contributions by introducing and studying various doped polynomials of a special nature.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have shown a growing interest in the exploration and investigation of ∆ h special polynomials, as evidenced by works such as [4,6,9,15,19]. Recently, Shahid Wani et al have made significant contributions by introducing and studying various doped polynomials of a special nature.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many mathematicians as the systematic study of degenerate versions of some special polynomials and numbers (see , Kim et al [5], Khan et al [6][7][8], and Sharma et al [9]) have been established due to Carlitz's degenerate version of Bernoulli polynomials given by (see [10,11])…”
Section: Introductionmentioning
confidence: 99%
“…where B n ðxÞ are the familiar Bernoulli polynomials (cf. [1,3,4,6,8,11,12,14,[16][17][18][19][20][21][22])…”
Section: Introductionmentioning
confidence: 99%